National Identity: Formation and Realisation Through Poetry - Urys, Tetiana; Kozak, Tetiana; Barabash, Svitlana (Տիգրան Մեծ)
National culture, especially literature, contains invaluable nation-building potential and is an effective factor in influencing the development of the national identity of the individual and the ethnic group as a whole. In the process of forming literary works, the author‟s consciousness and subconscious play an im-portant role, so they are not only one of the best ways of expressing a creative personality and a form of its reaction to events occurring in the outside world, but also one of the most important means of forming the national identity of the recipients. Therefore, such a literary work contains a modus of national identity. The main content of this concept in the literature is revealed in the article. Its theoretical components and their functional aspects in the text are defined and analysed.The modus ofnational identityis formulated as a way of realising the identity of one with his nation through certain aesthetic elements and structures at all levels of literarywork as an artistic system. Such element-dominants are motives, artistic imagery, lyrical character as the main expressionof the author‟s thoughts, as well as archetypes, symbols and place names.
Keywords: Philosophy of education